The right to the truth in international law - Ķilpe, Rēzija (Riga Graduate School of Law, 2023)
The analysis of the thesis sheds light on the right to the truth in in international law. The analysis conducted show that right to the truth is related to the obligation to provide truthful accounts of human rights violations and provides with detailed analysis of where the right to the truth in different ways can be found in legally binding and non-binding instruments. The analysis also examines the cases of the Inter-American Commission on Human Rights, Inter-American Court of Human Rights and European Court of Human Rights as regional bodies that have developed the scope of the right to the truth in international law over time. In addition, the thesis provides with an insight of the work and possible benefits of the establishment of a truth commission in time of a transition for a state - from time of unrest to time of peace, as well as to the development of the right to the truth.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; the right to the truth; Inter-American Commission on Human Rights; Inter-American Court of Human Rights; European Court of Human Rights